On Aphies Duponchel & Chevrolat, 1841, Amillarus Thomson, 1857, and Aprosopus sensu Guérin-Méneville (Coleoptera, Cerambycidae, Lamiinae) - Monné, Miguel A.; Santos-Silva, Antonio (Zootaxa, 2020)
The formal revalidation of Aphies Duponchel & Chevrolat, 1841, and A. erythrodera (type species of the genus) is provided. Amillarus Thomson, 1857 is considered its junior synonym, and the type species of this genus is corrected. Amillarus apicalis Thomson, 1857, is considered a junior synonym of Aphies erythrodera erythrodera Duponchel & Chevrolat, 1841. The date of the genus Aprosopus and its type-species, A. buquetii, as well as the authorship is changed. The date of the publication of the “Iconographie du Régne Animal de G. Cuvier” by Guérin-Méneville is questioned.